Protective effect of regular physical activity against diabetes‐related lower extremity amputation - Jae Won Kim; Kyung‐Do Han; Jun Hyeok Kim; Yoon Jae Lee (Journal of Diabetes)
Abstract Background Foot ulcers are a major complication of diabetes mellitus that increase morbidity and mortality in patients with diabetes, affect their quality of life, and increase the overall social burden. A considerable number of patients with diabetic foot ulcers (DFUs) require amputations every year. Methods This nation population–based study included 1 923 483 patients with diabetes who underwent regular health screening through the National Health Insurance Service during January 2009 and December 2012. We investigated the association between changes in physical activity (PA) status and the incidence of lower extremity amputation (LEA). Based on changes in PA status, participants were categorized into four groups: “remained inactive,” “remained active,” “active‐to‐inactive,” and “inactive‐to‐active.” Results Regular PA is an independent factor associated with a decreased risk of LEA in patients with diabetes. During the follow‐up period, 0.23% (n = 4454) of the patients underwent LEA. Compared with the “remained inactive” group, the “remained active” group were at the lowest risk of LEA (adjusted hazard ratio 0.5888; 95% confidence interval 0.524–0.66). A protective effect of regular PA against LEA was observed in the “remaining active” group. Conclusions Our findings suggest a protective role of PA against LEA in individuals with diabetes. This highlights the importance of recommending appropriate levels of PA for patients with diabetes. The study also showed a dose–response relationship, indicating that engaging in vigorous‐intensity PA was most beneficial, and higher amounts of PA may provide additional benefits.